Effective mapping of hypermedia high-level design primitives to implementation environments - Martínez López, Pablo E. (2001)
As the inherent complexity of hypermedia applications grows, the need for high-level design models and methods be omes imperative. There are several software engineering methods specially tailored for the domain of hypermedia applications, whith take into account the special needs of this kind of applications. However, the mapping of these high-level models to the implementation environments often results in a drasti loss of ri hness. This paper presents a domain-specific language which can be used to as an interme- diary between the software engineering models and the implementation environment. We show, through examples, how primitives found in diff erent hypermedia design methods an be mapped to our language, still preserving the original expresiveness. Our language also provides rendering fa ilities which allow to obtain working prototypes of the designs in a particular implementation platform.